Mineral Building Traditions in the Himalayas - Feiglstorfer, Hubert (2020)
This study gives fresh insight into the interaction between technical requirements, environmental resources and material implementation. It is the first scientific approach in studying the Himalayan earthen heritage in a wide scope and connecting material research and cultural heritage from various perspectives - in particular archaeology, architecture, research on materials and building techniques